Sovereign Debt Sustainability and Central Bank Credibility - Willems, Tim (IMF Working Papers; Working Paper ;, 2022)
This article surveys the literature on sovereign debt sustainability from its origins in the mid-1980s to the present, focusing on four debates. First, the shift from an "accounting based" view of debt sustainability, evaluated using government borrowing rates, to a "model based" view which uses stochastic discount rates. Second, empirical tests focusing on the relationship between primary balances to debt. Third, debt sustainability in the presence of rollover risk. And fourth, whether government borrowing costs below rates of growth ("r < g") generate a "free lunch" in the sense that debt sustainability does not require future primary surpluses. We argue that liquidity services provided by sovereign debt may indeed lead to a "free lunch", albeit of limited size. The value of such services depends on the credibility of the central bank, which can be accumulated via prudent policies and subsequently drawn on to allow for looser fiscal policy.